The teaching of languages in the Basque Country - Aliaga Ugarte, Rosa (Avances en Supervisión Educativa, 2010)
Our autonomous region holds two official languages: Castilian (i.e. Spanish) and Euskera (i.e. Basque). Both languages are widely used at school as first languages since the 1980s, from Infant Education to Compulsory Secondary Education and Bachillerato (post Compulsory Secondary Education lasting two years between 16 and 18 years of age). The introduction of a first foreign language (English in 99% of the cases) starts at the age of four, with a half an hour period three times a week until students are 7 years old. Students from 8 to 18 years old have two or three periods of 45 to 60 minutes each every week. The second foreign language (French, mainly) is offered for students to take it from the first form of Compulsory Secondary Education.